Estudio de prefactibilidad para la instalación de una planta de elaboración de un complemento alimenticio en polvo a base de harina de sangre de pollo y cacao - Urrelo Costa, Renzo Renato (2016)
The project involves the creation of a food supplement based on chicken blood flour and cocoa powder to help feed people, given the existing high levels of malnutrition. The development of the product is based in chicken blood flour for its high iron content compared with other, which represents a new differential factor.